Local translation in neuronal processes—in vivo tests of a "heretical hypothesis". Issue 3 (11th October 2013) - Perry, Rotem B.; Fainzilber, Mike; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT Intracellular trafficking and localization of mRNA is a fundamental feature of living cells, suggesting that localized mRNA translation should enable subcellular regulation of the proteome. Such localized regulation may be of particular importance in highly polarized cells such as neurons, where the requirement for a specific protein can be at a site far distant from the nucleus. Although dendritic and synaptic protein syntheses are well‐established phenomena, the apparent paucity of ribosomes in early studies on mature vertebrate axons generated significant skepticism regarding the possibility of protein synthesis within axons. Here, we summarize recent findings in genetically engineered mouse models that support a role for local translation in axonal expression of β‐actin and importin β1 in injured adult sensory neurons in vivo. These definitive confirmations of mammalian axonal protein synthesis in both transgenic and subcellular knockout models should direct further attention to the diverse roles suggested for local protein synthesis in axonal physiology. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 210–217, 2014